An Analysis of Persistent Non-Player Characters in the First-Person Gaming genre 1998-2007: a case for the fusion of mechanics and diegetics - Pinchbeck, Dan (Eludamos: Journal for Computer Game Culture, 2009)
This paper describes the results of an analysis of persistent non-player characters (PNPCs) in the first-person gaming genre 1998-2007. Assessing the role, function, gameplay significance and representational characteristics of these critical important gameplay objects from over 34 major releases provides an important set of baseline data within which to situate further research. This kind of extensive, genre-wide analysis is under-represented in game studies, yet it represents a hugely important process in forming clear and robust illustrations of the medium to support understanding. Thus, I offer a fragment of this illustration, demonstrating that many of the cultural and diegetic qualities of PNPCs are a product of a self-assembling set of archetypes formed from gameplay requirements.